Starting young: Multimodal gender presentation in children’s pop music - Maxwell, Kate (Septentrio Conference Series, 2019)
A recent quantitative study (Smith, Choueiti, and Pieper 2018) demonstrates the hegemonic discrimination in today’s popular music scene, particularly but not exclusively in gender and race. This paper builds on that study, taking it not only into a multimodal dimension (where musical and visual performances are taken into account), but also extending it to children’s popular music, here defined as popular music performed by children for an audience and market primarily made up of children and their guardians. The annual Norwegian popular music competition for children aged 8-15 Melodi Grand Prix Junior (MGP Jr) is the children’s equivalent of the adult competition to be Norway’s entry in the Eurovision Song Contest (ESC). It has been running since 2004, with 10 entries in each final, and those from 2007 onwards are available for public viewing on the national television channel’s website (tv.NRK.no). The resulting 130 songs thus provide a meaningful corpus from which to study current and recent multimodal gendered presentations of child performers. Preliminary multimodal gender analyses (cf Maxwell and Mittner 2018) show that the performances are based around traditional gender binaries (i.e. boys and girls). While both presented genders sing, except for rare exceptions it is only boys who play instruments. This both complements and contrasts the study of the ESC (Isaksen forthcoming) which also shows a clear dominance of singing, particularly among female and female-presenting artists (including drag queens). When these results from children’s pop music and from the ESC are set in relation to Smith, Choueiti, and Peiper 2018 in an interdisciplinary mixed methods approach, it is clear to see that the discrimination in the industry not only begins at a young age, it is also presented as normal, indeed attractive, to child viewers. This is borne out by the decreasing uptake of music tuition at Norwegian kulturskoler (the provider of state-sponsored lessons in the arts), particularly among school-age girls (Utdanningsdirektøret 2017). In this paper I will present multimodal analyses of a selection of songs from MGP Jr in order to provide both examples of and exceptions to the norms shown by the statistics. In addition, an analysis of the (gendered) presentations of standard Norwegian instrument textbooks (cf Blix 2018) provides background context, with an emphasis on the gendered meanings that surround children in their everyday musical lives. With thanks to Matilda Maxwell (age 11), aspiring instrumentalist, fan of MGP Jr, and research assistant.